PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN HASILBELAJAR IPS MATERI KEDATANGAN BANGSA BARAT KELAS VI SD NEGERI 16 KOTA TERNATE - Saleh, Lily (Jurnal GeoCivic, 2024)
The aim of this research is to identify the process of implementing the discovery learning model in improving social studies learning outcomes regarding the arrival of western nations in class VI SD Negeri 16 Kota Ternate. This research was carried out using a qualitative approach with the type of classroom action research (PTK). The sequence of research activities includes: (1) planning, (2) implementation, (3) observation, (4) reflection. Data collection uses tests, observation, interviews and documentation. Meanwhile, for the analysis, researchers used qualitative descriptive analysis techniques. The research object is the sixth grade students of SD Negeri 16 Kota Ternate. The results of the research show that the application of the discover learning learning model in social studies lessons regarding the arrival of western nations can improve student learning outcomes, especially in class VI at SD Alkhairaat 2 Tobelo. This can be seen in cycle I, 27% of students were said to have completed or 6 students, with an average score of 49.09%, while in cycle II there was an increase in students who completed 72% or 16 students with an average score of 77.72%. . Cycle I student activities received an average score of 66% and cycle II an average score of 86%. And teacher activities in cycle I got an average score of 65% and in cycle II got an average score of 86%. Thus, the application of the discovery learning model regarding the event of the arrival of the Westerners can improve social studies learning outcomes for class VI students at SD Al-Khairaat 2 Tobelo.